The coemergence of the neotropical otter in the constructed reality of UHE Caconde (Research, Society and Development, 2023)
Emergy analysis can be applied to establish the relationship between the natural and the economic system, in the analysis and conservation of biodiversity and the sustainability of large bodies of water. This research aims to investigate the occurrence of neotropical otters in the UHE Caconde through a systemic analysis based on the flow of energy between the different ecological compartments. Data were obtained from several sources, including local official statistical yearbooks, inventories, dissertations, theses, published articles, and UHE Caconde reports. The intensity of the presence of the neotropical otter in the sampling sites is determined by the positive or negative record of the species and the number of excrements over time. Of the 56 points monitored, 50% reported the presence of the species. Results indicate that there was a significant difference in the number of excrement over the months. The measurement of biodiversity in joules, positions mammals first with 2.0E+23 seJ/espécie, followed by amphibians (1.3E+23 seJ/espécie), reptiles (1.0E+23 seJ/espécie), birds (5.2E+22 seJ/espécie), and fish (1.1E+22 seJ/espécie). Renewable sources are dominated by geopotential rain and transpiration, 233 and 139 million emdollars, respectively. These energy sources are followed by potential chemical rain (at em$139 million), surface water runoff (at em$98 million), and wind (at em$268 thousand). The presence of Lontra longicaudis in the lake of Caconde and its main tributaries has as its main feature the dependent origin, which results from researchers' experience and vision of the environment, and a trophic network, which follows an energy order in the system.